2019
DOI: 10.1103/physrevb.100.085406
|View full text |Cite
|
Sign up to set email alerts
|

Berry curvature induced thermopower in type-I and type-II Weyl semimetals

Abstract: Berry curvature acts analogously to a magnetic field in the momentum-space, and it modifies the flow of charge carriers and entropy. This induces several intriguing magnetoelectric and magnetothermal transport phenomena in Weyl semimetals. Here, we explore the impact of the Berry curvature and orbital magnetization on the thermopower in tilted type-I and type-II Weyl semimetals, using semiclassical Boltzmann transport formalism. We analytically calculate the full magnetoconductivity matrix and use it to obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 83 publications
4
39
1
Order By: Relevance
“…This manifests in the magnetothermal experiments in the form of positive magnetothermopower and positive magnetothermal conductivity [26][27][28][29], both of which have also been observed in recent experiments [30,31]. In addition to their manifestations in longitudinal magnetotransport, CAs have also been shown to give rise to the planar Hall effects in all transport coefficients [29,[32][33][34][35][36][37][38][39][40]. Recently, we predicted another anomaly, the thermal chiral anomaly in which a temperature gradient collinear with the magnetic field gives rise to charge and energy imbalance between the opposite chirality Weyl fermions [29].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…This manifests in the magnetothermal experiments in the form of positive magnetothermopower and positive magnetothermal conductivity [26][27][28][29], both of which have also been observed in recent experiments [30,31]. In addition to their manifestations in longitudinal magnetotransport, CAs have also been shown to give rise to the planar Hall effects in all transport coefficients [29,[32][33][34][35][36][37][38][39][40]. Recently, we predicted another anomaly, the thermal chiral anomaly in which a temperature gradient collinear with the magnetic field gives rise to charge and energy imbalance between the opposite chirality Weyl fermions [29].…”
Section: Introductionsupporting
confidence: 65%
“…So far we have explored the impact of CAs in the longitudinal magnetotransport coefficients. However, it has been shown that the origin of planar Hall effects and anisotropic longitudinal transport coefficients in nonmagnetic materials can also be related to CAs [32][33][34][35][36]. Here, we explore the impact of quantized LLs, on all the planar Hall transport coefficients and explore the possibility of quantum oscillations in them.…”
Section: Planar Hall Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…To explore the impact of anomalies on longitudinal magneto-resistance (MR), we define generic MR γ ≡ γ(B)/γ(0) − 1, where γ denotes the transport coefficients: σ, α,ᾱ, κ or S. To evaluate the MR, we need to add the Drude components to the respective transport coefficients. Evaluating the Drude components for each Weyl node [39], we have {σ s 0 , α s 0 ,κ s 0 } =…”
mentioning
confidence: 99%
“…Similarly, in response to a temperature gradient, without any external magnetic field, it generate a transverse Hall voltage, known as the anomalous Nernst effect [9,[12][13][14]. Coupled with the Boltzmann transport theory, the modified semiclassical equations have been employed to study transport in topological insulators [15], Chern Insulators [16], Weyl Semi-Metals [13,14,[17][18][19][20][21][22], Kondo Insulators [23], Rashba systems [24,25], optical lattices and quasicrystals [26,27], superconductors [28], non-Hermitian systems [29,30], as well as in various other systems [31][32][33][34][35][36][37]. Non-linear effects in transport have also been studied within this formalism [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%